Quality of Recycled Aggregates and Compressive Strength of No-Fines Recycled-Aggregate Concrete - Dahri, S. A.; Memon, B. A.; Oad, M.; Bhanbhro, R.; Rahu, I. A. (Engineering, Technology & Applied Science Research, 2021)
This research paper presents the laboratory investigations of the compressive strength of no-fines concrete made with demolished waste as coarse aggregates used in percentages from 20% to 100%. The basic properties of aggregates were determined. Sieve analysis of both conventional and recycled aggregates was conducted to ensure the existence of well-graded aggregates in concrete. Nine concrete mixes were designed with an aggregate-cement ratio of 4. Additionally, three batches were prepared (conventional, recycled, conventional no-fines concrete) and the results were compared. For all mixes, the water-cement ratio was equal to 0.5. In each batch, 5 cylinders of standard size (total 60 samples) were prepared and cured for 28 days. The weight of the specimens was determined and compressive strength was checked in a Universal Testing Machine under gradually increasing load. A decrease in weight and compressive strength was recorded for the batches of the proposed concrete. Results show that at 40% replacement level the loss of compressive strength is 19% and the weight reduction of the samples was equal to 9%.